2016
DOI: 10.1021/acs.jpcb.6b01900
|View full text |Cite
|
Sign up to set email alerts
|

Transient Conformational Changes of Sensory Rhodopsin II Investigated by Vibrational Stark Effect Probes

Abstract: Sensory rhodopsin II (SRII) is the primary light sensor in the photophobic reaction of the halobacterium Natronomonas pharaonis. Photoactivation of SRII results in a movement of helices F and G of this seven-helical transmembrane protein. This conformational change is conveyed to the transducer protein (HtrII). Global changes in the protein backbone have been monitored by IR difference spectroscopy by recording frequency shifts in the amide bands. Here we investigate local structural changes by judiciously ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…Mol. a Local mode contributions b 1-1 88.2% C1-O4, 11.8% H2-C1-H3 1-2 83.4% C1-O4, 10.4% (C1-F2, C1-F3), 6.2% F2-C1-F3 1- 3 93.1% C1-O4 1- 4 94.7% C1-O4 1- 5 85.5% C1-O4 1- 6 76.3% C3-O8, 18.7% (C3-C1, C3-C2) 1- 7 82.0% C3-O11, 6.9% C2-C3-C4 1- 8 82.4% C4-O14, 8.3% C3-C4-C5 1- 9 82.3% C1-O17, 5.2% C6-C1-C2 1- 10 77.4% C1-O2, 5.3% C3-C1-C7 1- 11 67.6% C1-O2, 7.0% C4-C1-C7, 5.6% C4-C1, 5.6% C7-C1 1- 12 77.7% C5-O10, 7.3% C4-C5-C6 1- 13 79.7% C1-O2, 6.2% C14-C1-C3 1-14 79.2% C1-O2, 6.2% C3-C1-C14 1- 15 89.2% C1-O2 1- 16 90.5% C1-O2 1- 17 71.5% C1-O16, 10.7% N11-C1-C4, 7.5% N11-C1 1- 18 80.6% C1-O2, 6.4% N3-C1, 6.4% N5-C1 1- 19 91.2% C1-O2 1-20 81.9% C5-O6, 6.1% C5-C1, 5.5% O7-C5-C1 1-21 76.0% C1-O2, 7.1% C8-C1-O3, 5.7% C8-C1 1- 22 87.2% C1-O2, 5.3% C1-C6 1- 23 75.7% C1-O2, 6.9% N7-C1, 6.8% N7-C1-C3 1- 24 93.3% C1-O2, 6.7% C1-Fe39 1- 25 94.0% C1-O2 92.5% C9-N10, 7.5% C9-S1 2-8 89.9% C1-N2, 10.1% C3-C1 2-9 45.1% N9-C7, 45.1% C8-N10 2-10 44.1% C1-N2, 44.1% C3-N4, 11.6% (C3-C7, C5-C1) 2- 11 88.3% C12-N13, 11.3% C12-C3 2- 12 88.4% N2-C1, 11.3% C3-C1 2- 13 88.3% C1-N2, 11.5% C1-C3 2-14 92.8% C13-N14, 7.2% C13-S12 2- 15 87.3% N7-C6, 12.5% C4-C6 2- 16 94.2% N2-C1, 5.8% Se3-C1 2-17 93.7% C1-N2, 6.3% C1-Se3…”
Section: Group 1: C=o and C≡o Probesmentioning
confidence: 99%
See 2 more Smart Citations
“…Mol. a Local mode contributions b 1-1 88.2% C1-O4, 11.8% H2-C1-H3 1-2 83.4% C1-O4, 10.4% (C1-F2, C1-F3), 6.2% F2-C1-F3 1- 3 93.1% C1-O4 1- 4 94.7% C1-O4 1- 5 85.5% C1-O4 1- 6 76.3% C3-O8, 18.7% (C3-C1, C3-C2) 1- 7 82.0% C3-O11, 6.9% C2-C3-C4 1- 8 82.4% C4-O14, 8.3% C3-C4-C5 1- 9 82.3% C1-O17, 5.2% C6-C1-C2 1- 10 77.4% C1-O2, 5.3% C3-C1-C7 1- 11 67.6% C1-O2, 7.0% C4-C1-C7, 5.6% C4-C1, 5.6% C7-C1 1- 12 77.7% C5-O10, 7.3% C4-C5-C6 1- 13 79.7% C1-O2, 6.2% C14-C1-C3 1-14 79.2% C1-O2, 6.2% C3-C1-C14 1- 15 89.2% C1-O2 1- 16 90.5% C1-O2 1- 17 71.5% C1-O16, 10.7% N11-C1-C4, 7.5% N11-C1 1- 18 80.6% C1-O2, 6.4% N3-C1, 6.4% N5-C1 1- 19 91.2% C1-O2 1-20 81.9% C5-O6, 6.1% C5-C1, 5.5% O7-C5-C1 1-21 76.0% C1-O2, 7.1% C8-C1-O3, 5.7% C8-C1 1- 22 87.2% C1-O2, 5.3% C1-C6 1- 23 75.7% C1-O2, 6.9% N7-C1, 6.8% N7-C1-C3 1- 24 93.3% C1-O2, 6.7% C1-Fe39 1- 25 94.0% C1-O2 92.5% C9-N10, 7.5% C9-S1 2-8 89.9% C1-N2, 10.1% C3-C1 2-9 45.1% N9-C7, 45.1% C8-N10 2-10 44.1% C1-N2, 44.1% C3-N4, 11.6% (C3-C7, C5-C1) 2- 11 88.3% C12-N13, 11.3% C12-C3 2- 12 88.4% N2-C1, 11.3% C3-C1 2- 13 88.3% C1-N2, 11.5% C1-C3 2-14 92.8% C13-N14, 7.2% C13-S12 2- 15 87.3% N7-C6, 12.5% C4-C6 2- 16 94.2% N2-C1, 5.8% Se3-C1 2-17 93.7% C1-N2, 6.3% C1-Se3…”
Section: Group 1: C=o and C≡o Probesmentioning
confidence: 99%
“…Below each structure, a label as n-m is given in blue, n denotes the group number (reflecting the type of VSE probe bond), and m is the number of this molecule in this group. Vibrational probe labels with superscripts are taken from the literature (a [4,10,50,51], b [10,18,24,27], c [24], d [18,50], e [5,10,18,26,27,50], f [18], g [26,50,51], h [102], i [20]). The corresponding performance score as VSE probe is given in purple.…”
Section: Groups 2 and 3: C≡n And S=o Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged photocycle of NpSRII similar to bR is suitable for probing the photointermediate state during the photocycle with FTIR spectroscopy. Crystal structure of NpSRII (Luecke et al, 2001;Gordeliy et al, 2002) and spectroscopic studies on the photocycle of NpSRII under blue light illumination (Hirayama et al, 1992;Engelhard et al, 1996;Chizhov et al, 1998;Furutani et al, 2002;Hein et al, 2003;Furutani et al, 2004;Iwamoto et al, 2004;Bergo et al, 2005;Mironova et al, 2005;Jiang et al, 2008;Jiang et al, 2010;Tateishi et al, 2011;Mohrmann et al, 2016;Pfitzner et al, 2018) have been previously reported. Given this literature precedent, we record the FTIR difference spectrum of NpSRII under NIR light illumination.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to correct eq A, Mohrmann et al used an incorrect equation (eq 1 in ref 1) related to the form that describes the effect of an external electric field, F⃗ ext , on an isotropic immobilized sample. As described in detail in refs 5 and 6, complex lineshapes occur in field-on minus field-off difference spectra for an isotropic immobilized sample in an external electric field because the probe has no fixed orientation with respect to the external field; an analysis of these lineshapes gives |Δ μ⃗ probe |, the change in polarizability (typically small for vibrational transitions), and other electro-optic parameters.…”
mentioning
confidence: 99%